2015
DOI: 10.1177/0284185114520860
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound using real-time contrast harmonic imaging in invasive breast cancer: comparison of enhancement dynamics with three different doses of contrast agent

Abstract: The optimal way to evaluate kinetic features of invasive breast tumors using real-time CEUS is with an injection of contrast agent of either 2.4 mL or 4.8 mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A total of 2.4 mL of the contrast agent was used as an establish required dose for using a 9 MHz probe and due to our previous experience (12,14,15) and administrated manually as a bolus (2 s) followed by a flush of 10 cc saline solution. The examination was recorded in a contrast side/side imaging mode loop from the start of the bolus and for a 120-s period.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 2.4 mL of the contrast agent was used as an establish required dose for using a 9 MHz probe and due to our previous experience (12,14,15) and administrated manually as a bolus (2 s) followed by a flush of 10 cc saline solution. The examination was recorded in a contrast side/side imaging mode loop from the start of the bolus and for a 120-s period.…”
Section: Methodsmentioning
confidence: 99%
“…However, the quantitative parameters are subject to considerable variations caused by factors such as scanner settings, microbubble type, handling, and administration, or physiological variations as reviewed by Tang et al and summed in the European guidelines for quantitative CEUS (168,169). Therefore, evaluation of the reproducibility of the quantitative outcomes is crucial to consider in the planning of future clinical studies (170,171).…”
Section: Contrast-enhanced Ultrasoundmentioning
confidence: 99%
“…There was an interval of 10 min between the two examinations in every patient. 9 To eradicate contrast bubbles within the lesion, high-mechanical index (MI) waves were used during this interval. Every CEUS process was recorded for 180 s until no apparent contrast agent could be observed.…”
Section: Image Analysismentioning
confidence: 99%
“…We also found that transducers used for conventional breast ultrasound are different from transducers for breast CEUS. 9,10 The aim of this study was to compare the effectiveness of transducers with different frequencies in detecting local blood perfusion defects and surrounding vessels in the same breast lesions of the same patients. This study will assess the influence of different transducers on the detection outcomes of breast CEUS and try to find a way to improve the diagnostic efficacy of breast CEUS.…”
Section: Introductionmentioning
confidence: 99%